KONTROL FREKUENSI DAN TEGANGAN GENERATOR MENGGUNAKAN METODE JARINGAN SYARAF TIRUAN - Abdul Hafid; Efendi Muchtar (Teknik Elektro Politeknik Negeri Padang, 2009)
This paper discusses artificial neural network to controlling frequency and voltage generator using control system based – on diagonal recurrent neural network. Reference model for purpose controlling generator frequency and voltage i.e. at settling time 50 Hz and 380 V (line-to line) respectively. Observation shows that control system based-on diagonal recurrent neural network has good performance in the case of controlling frequency and voltage of plant generator.